1980
DOI: 10.4141/cjps80-096
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Coleoptile Length and Culm Length in Barley

Abstract: coleoptile length and culm length in barley. Can

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Positive relationships between straw length and coleoptile length have been demonstrated in some barley studies (Takahashi 1946;Ceccarelli et al 1980) but not in others (Ceccarelli et al 1980;Bacaltchuk and Ullrich 1983;Dolnicki 1983;Hughes and Mitchel 1987;Takeda and Takahashi 1999;Singh et al 2002). As with the later studies we could not find evidence to support the view that short cultivars have short coleoptiles or that cultivars with a prostrate early growth habit have shorter than average coleoptiles (data not presented).…”
Section: Plant Height Genes and Coleoptile Lengthmentioning
confidence: 88%
See 2 more Smart Citations
“…Positive relationships between straw length and coleoptile length have been demonstrated in some barley studies (Takahashi 1946;Ceccarelli et al 1980) but not in others (Ceccarelli et al 1980;Bacaltchuk and Ullrich 1983;Dolnicki 1983;Hughes and Mitchel 1987;Takeda and Takahashi 1999;Singh et al 2002). As with the later studies we could not find evidence to support the view that short cultivars have short coleoptiles or that cultivars with a prostrate early growth habit have shorter than average coleoptiles (data not presented).…”
Section: Plant Height Genes and Coleoptile Lengthmentioning
confidence: 88%
“…Another advantage of the sdw4 gene is that it is not associated with delayed maturity like the sdw1 gene (Zhang and Zhang 2003). Ceccarelli et al (1980) suggested that the association between coleoptile length and straw length can be broken with adequate population size in breeding programs.…”
Section: Plant Height Genes and Coleoptile Lengthmentioning
confidence: 98%
See 1 more Smart Citation
“…Deep seed placement and reduced coleoptile elongation in the predominantly hot soil can have a potentially devastating impact on stand establishment [55]. It was reported that seed size had little impact on coleoptiles lengths in barley but not in wheat and oats [9]. Studies have demonstrated a strong association between coleoptiles length and seedling emergence with shallow [14] and deep sowing [19, 29, 32, 50 and 61].…”
Section: Significance Of Long Coleoptile Fig 1 Schematic Presentatiomentioning
confidence: 99%